NANOPARTÍCULAS DE PRATA E SAPONINAS AFETAM A GERMINAÇÃO DE SEMENTES DE ALGODOEIRO - Gossypium sp L. (MALVACEAE) CULTIVAR BRANCO? - SILVA, Johnatan Vieira da,; ARRUDA, Gilberto José de,; SANTIAGO, Etenaldo Felipe. (felipe@uems.br, (ANAIS DO ENIC, 2024)
-